Conceptualizing After-School Literacy Intervention in Trinidad & Tobago: A Comparative Study - Sammy, Hannah Sundari (2018)
Given the everchanging educational landscape and challenges that contemporary education systems face, it is worth reflecting on alternative contexts, strategies and frameworks for learning. This study engages this notion by investigating after-school literacy programs around the world, with the aim of conceptualizing such programs in Trinidad and Tobago. To do so, an international comparative study was conducted which compared programs from developed and developing regions, through the process of thematic analysis. The goal of this research was to determine elements of effective literacy programs and theorize the relevance and place that these held within the setting of Trinidad and Tobago. The findings revealed eight themes among the sample which were further analysed to form a conceptual framework of after-school literacy in Trinidad and Tobago. Finally, this study posits that for after-school literacy intervention in Trinidad and Tobago to be effective, programs should have adaptive characteristics, use cultural relevant pedagogies and encourage family-school-community partnerships.